Modelling and Simulation of Transport Mechanisms of Electro-Migration and Diffusion of Ionic Species in the Concrete through Meshless Methods - Flores Cortez, Mizhaeel Semei; Muñoz Gómez, José Antonio; Nuñez, Rosa Elba; Barrios, Carlos P; Castorena González, José Humberto (ECS transactions, 2017)
The transport of ions such as chloride ion through the concrete has been the subject of study, because the entrance of these, affects the useful life of the structure. The mechanism of ionic transport is described by the Nernst-Planck equation and to solve the problem numerical techniques such as the Finite Difference Method (MDF) or Finite Element (MEF) are used which require a meshing process and a higher cost Computational. In this work, relatively new methods such as the Radial Base Functions (FBR) method and the Fundamental Solution Method (MSF) were applied, which do not require a mesh to solve the ion transport problem.